Highly enhanced gas-sensing properties of indium-doped mesoporous hematite nanowires. (September 2018) - Chen, H.D.; Jin, K.L.; Wang, P.F.; Xu, J.C.; Han, Y.B.; Jin, H.X.; Jin, D.F.; Peng, X.L.; Hong, B.; Li, J.; Yang, Y.T.; Gong, J.; et al.
Abstract: Mesoporous indium (In)-doped hematite (α-Fe2 O3 ) nanowires were synthesized with mesoporous SBA-15 silica as a hard template, and then the influence of In dopant on the microstructure and gas-sensing performance was investigated in detail. With characterization by transmission electron microscopy, X-ray diffraction, UV–vis spectroscopy, and nitrogen physisorption experiments, it was shown that the average grain size increased for up to 1 mol% In dopant and then decreased with increasing In dopant content, while the surface area changed in the inverse manner. Because of the low melting point of In, In acted as a fluxing agent and entered the α-Fe2 O3 lattice when the In content was low, and the average grain size increased. With higher In content, In precipitated out the lattice and existed at the grain boundary, and the grain size decreased. It is concluded that In in the lattice increased lattice distortion and In at the boundary increased the surface area and oxygen vacancies, which were both beneficial for improving the gas-sensing performance. The response of In-doped α-Fe2 O3 nanowires increased by about 30%–50% as compared with that of pure α-Fe2 O3 nanowires. The gas sensor based on 3 mol% In–doped α-Fe2 O3 nanowires exhibited the best gas response and a rapid response-recovery time toward ethanol at the optimum temperature. Owing to the same valence, In dopant affected only the microstructure and components of the α-Fe2 O3 lattice, which was necessary to improve the gas-sensing behavior. Graphical abstract: Highlights: Mesoporous indium-doped α-Fe2 O3 nanowires were synthesized by a nanocasting method. Indium with the same valence as iron affected only the microstructure of α-Fe2 O3 nanowires. The average grain sizes increased firstly and then decreased. Indium dopant increased the oxygen vacancies of α-Fe2 O3 nanowires. The response of indium-doped α-Fe2 O3 nanowires increased by about 30%–50%.